Students stress patterns in a Kenyan socio-cultural and economic context: toward a public health intervention - Mutiso Victoria N.; Ndetei David M.; Muia Esther N.; Musyimi Christine; Masake Monicah; Osborn Tom L.; Sourander Andre; Weisz John R.; Mamah Daniel (Nature Research, 2025)
This study aimed at determining the prevalence of stress, different types of stress, their severity and their determinants in Kenyan university, college and high school students. The following tools were administered to 9741 students: (1) Researcher-designed socio-demographic tool, (2) Psychiatric Diagnostic Screening Questionnaire (PDSQ) for psychiatric disorders, (3) WERC Stress Screen for stress, (4) Washington Early Recognition Center Affectivity and Psychosis (WERCAP) screen for psychosis and affectivity, (5) Wealth Index Questionnaire for economic indicators. Descriptive analysis for the prevalence of different types of stress and inferential analysis for stress and independent variables were done. Significant variables (p < 0.05) were fitted into generalized linear model to determine independent predictors. The mean age of the respondents was 21.4 years (range 16–43). Money issues were the commonest stressors while alcohol and drug use were the least. The independent predictors of stress were females, college students and use of gas stove. In conclusion, up to 30% of the students suffer from mild to severe stress. The students experience a wide range of stressors. The most important stressors include money and finances, family related problems and concerns about their future. Our findings suggest a public health approach to create stress awareness in students.